Integrasi Terrestrial Laser Scanning Dan Dstretch Untuk Pelestarian Berbasis Digital Pada Situs Kubur Bilik Batu Di Dataran Tinggi Pasemah, Sumatera Selatan - Halimun, Mentari; Permana, R Cecep Eka; Leihitu, Irsyad; Dwi Hanggoro, Pramudianto Dwi Hanggoro (PURBAWIDYA, 2025)
The Pasemah Highlands in South Sumatra host a significant concentration of ancestor-worship culture remains, particularly stone chamber tombs decorated with paintings. These monuments face increasing vulnerability due to natural factors, material degradation, and human activities. This study explores the integration of Terrestrial Laser Scanning (TLS) and DStretch as a digital documentation approach and examines its implications for adaptive preservation strategies. TLS provides high-precision three-dimensional spatial data for recording site geometry and structural conditions, while DStretch enhances faint pigments and motifs on chamber walls. The findings demonstrate that combining TLS and DStretch not only enriches archaeological documentation in both spatial and visual dimensions but also generates a comprehensive dataset to support evidence-based conservation. This integration strengthens adaptive preservation by enabling condition monitoring, documentation standardization, and community engagement in heritage management. The study highlights integrative digital documentation as a methodological innovation that contributes significantly to the sustainable preservation of ancestor-worship culture sites in Indonesia.